Acute changes in serum and skeletal muscle steroids in resistance-trained men - Vechin, Felipe C.; Vingren, Jakob L.; Telles, Guilherme D.; Conceicao, Miguel S.; Libardi, Cleiton A.; Lixandrao, Manoel E.; Damas, Felipe; Cunha, Telma F.; Brum, Patricia C.; Riani, Luiz A.; Ugrinowitsch, Carlos (Frontiers in Endocrinology, 2023)
We aimed to determine whether resistance exercise-induced increases in serum steroid hormone concentrations are accompanied by enhanced skeletal muscle steroid concentrations, or whether muscle contractions per se induced by resistance exercise can increase intramuscular steroid concentrations. A counterbalanced, within-subject, crossover design was applied. Six resistance-trained men (26 ± 5 years; 79 ± 8 kg; 179 ± 10 cm) performed a single-arm lateral raise exercise (10 sets of 8 to 12 RM - 3 min rest between sets) targeting the deltoid muscle followed by either squat exercise (10 sets of 8 to 12 RM - 1 min rest) to induce a hormonal response (high hormone [HH] condition) or rest (low hormone [LH] condition). Blood samples were obtained pre-exercise and 15 min and 30 min post-exercise; muscle specimens were harvested pre-exercise and 45 min post-exercise. Immunoassays were used to measure serum and muscle steroids at these time points. In the serum, only cortisol significantly increased after the HH protocol. There were no significant changes in muscle steroid concentrations after the protocols. Our study provides evidence that serum steroid concentration increases (cortisol only) seem not to be aligned with muscle steroid concentrations.